Legume-cereal mixtures ensiling in Sardinia - Sulas C.; Ruda P.; Salis M.; Atzori A.S.; Correddu F.; Cannas A.; Carroni A.M. (New approaches for grassland research in a context of climate and socio-economic changes, 2012)
Animal feeding accounts more than 50% of farm production costs, often principally due to the protein component acquisition. Cereals and legume mixtures silage could represent an interesting source of high nutritive value forage in non-irrigated lands. Mixtures can provide an adequate proportion of nitrogen and carbohydrates in the ensiling substrates, needed to help lactic fermentation and pH reduction, essential to the conservation process. The aim of this trial was to compare silage of three leguminous-triticale mixtures, in order to obtain a preliminary evaluation for high quality and stable forages production, destined to ruminant feeding in Mediterranean areas. The trial was carried out in Sardinia between autumn 2010 and spring 2011. Mixtures of Triticale (Triticosecale WittMack)-white lupin (Lupinus albus L.), triticale-pea (Pisum sativum L.) and triticale-faba bean (Vicia faba minor L.) were evaluated. After six months of ensiling process in glass jars, silage was analyzed, by determining: pH, dry matter, fibrous fractions, crude protein, ash content, NFC+lipids and estimated DM digestibility. Mixtures with pea and triticale Amarillo reached the highest content of DM. When used in mixtures with triticale and in respect to lupin and pea, faba bean obtained the lowest values of NDF, ADF, and ADL and the highest content of NFC+lipids. Faba bean was also able to maintain the highest protein content. Considering the CP content of silage, the 30:70 seeding ratio resulted the more convenient. A more detailed evaluation of obtained results should be performed also considering the biomass production per hectare at farm level.
14. Meeting of the FAO-CIHEAM Subnetwork on Mediterranean Forages and Fodder Crops, 2012/10/03-06, Samsun (Turkey)